The analysis of The Global Index of Innovation of Serbia and Bosnia and Herzegovina - Ćosić Miilivoje; Tomić Ljiljana; Mesarević Aleksandra (Trendovi u Poslovanju)
In modern business conditions most countries of the world have increasingly been adopting policies and strategies that encourage innovation, because they have realized that without systematically encouraging the development of innovation there is no global competitiveness. The Global Innovation Index (GII) is the index which measures the achieved level of innovation of certain countries, based on two sub-indices: the Index of Innovation Inputs and the Index of Innovation Outputs. Both sub-indices include certain pillars, so that the Index of Innovation Inputs includes five pillars, while the Index of Innovation Outputs includes two pillars. This paper analyzes the ranking results of Serbia and Bosnia and Herzegovina according to the global Innovation Index, which is published every year by the World Intellectual Property Organization (WIPO), as well as all the pillars of the Global Innovation Index for both countries.